Intelligent Engineering Informatics Proceedings of the 6th International Conference on FICTA - Bhateja, Vikrant; Coello Coello, Carlos A.; Satapathy, Suresh Chandra; Pattnaik, Prasant Kumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book presents the proceedings of the 6th International Conference on Frontiers of Intelligent Computing: Theory and Applications (FICTA 2017), held in Bhubaneswar, Odisha. The event brought together researchers, scientists, engineers, and practitioners to exchange their new ideas and experiences in the domain of intelligent computing theories with prospective applications to various engineering disciplines. The book is divided into two volumes: Information and Decision Sciences, and Intelligent Engineering Informatics.  This volume covers broad areas of Intelligent Engineering Informatics, with papers exploring both the theoretical and practical aspects of various areas like ANN and genetic algorithms, human-computer interaction, intelligent control optimisation, intelligent e-learning systems, machine learning, mobile computing, multi-agent systems, etc. The book also offers a valuable resource for students at the post-graduate level in various engineering disciplines.
1. Assessment of Integrity Auditing Protocols for Outsourced Big Data -- 2. A New Term Weight Measure for Gender Prediction in Author Profiling -- 3. Image Encryption Based on Arnold Cat Map and GA operator. -- 4. SVM Based Method for Identification and Recognition of Faces by using Feature Distances -- 5. Content-Aware Reversible Data Hiding: Urhs -- 6. Application of TF-IDF Feature for Categorizing Documents of Online Bangla Web Text Corpus -- 7. An Ensemble Learning based Bangla Phoneme Recognition System using LPCC-2 Features -- 8. Solving Uncapacitated Facility Location Problem Using Monkey Algorithm -- 9. AISLDr: Artificial Intelligent Self-Learning Doctor -- 10. Kernel-Based Naive Bayes Classifier For Medical Predictions -- 11. AKM - Augmentation Of K-Means Clustering Algorithm for Big Data -- 12. Face Recognition Using Local Binary Pattern-Blockwise Method -- 13. Social Group Optimization (SGO) for Clustering in Wireless Sensor Networks -- 14. Implementation of High Performance FloatingPoint Divider using Pipeline Architecture on FPGA -- 15. GA_DTNB: A Hybrid Classifier for Medical Data Diagnosis -- 16. Applications of Spiking Neural Network to Predict Software Reliability -- 17. An Optimized Rendering Solution for Ranking Heterogeneous VM Instances -- 18. Gender prediction in Author Profiling using ReliefF Feature Selection Algorithm -- 19. Optimal Coordination of Overcurrent Relays using Simulated Annealing and Brute Force Algorithms -- 20. The Close-Loop Antenna Array Control System For Automatic Optimization in LTE and 3G Network -- 21. Tumour Classification in Graph-Cut Segmented Mammograms using GLCM Features fed SVM -- 22. Improving Feature Selection using Elite Breeding QPSO on Gene dataset for Cancer Classification -- 23. Epileptic Seizure Mining Via Novel Empirical Wavelet Feature with J48 and KNN Classifier -- 24. Gallbladder Shape Estimation using Tree Seed Optimization tuned Radial Basis Function Network for Assessment of Acute Cholecystitis -- 25. Materialized View Selection using Backtracking Search Optimization Algorithm -- 26. Fractal coding for texture, satellite and gray scale images to reduce searching time and complexity -- 27. Hybrid Genetic Algorithm Differential Evolution Approach for Localization in WSN -- 28. Local Tetra Pattern Based Fruit Grading Using Different Classifiers -- 29. An Integrated Approach Incorporating Non Linear Dynamics and Machine Learning for Predictive Analytics and Delving Causal Interaction -- 30. Adaptive Channel Equalization using Decision Directed & Dispersion Minimising Equalizers trained by Variable Step size Firefly Algorithm -- 31. A Study on Wrapper Based Feature Selection Algorithm for Leukemia Dataset -- 32. Wind Converter Monitoring Using ANN -- 33. Analysis and Prototype Sequences of Face Recognition Techniques in Real time Picture Processing -- 34. Closed-set Text-independent Automatic Speaker Recognition System using VQ/GMM -- 35. Differential Evolution based Sensor Allocation for Target Tracking Application in Sensor-Cloud -- 36. Design & Analysis of Kite for Producing Power up to 2.6 Watts -- 37. RSSI based Posture Identification for Repeated and Continuous Motions in Body Area Network -- 38. Old Age Health Risk Prediction And Maintenance Via IoT devices and Artificial Neural Network -- 39. Computational intelligence based Chaotic Time series Prediction using Evolved Neural Network -- 40. Intelligent and Integrated Books Recommendation and Best Price Identifier System using Machine Learning -- 41. Online Handwritten Bangla Character Recognition using CNN: A Deep Learning Approach -- 42. A Study on Clustering Algorithms for Large, Unstructured and Semi- structured Data -- 43. A chaotic steganography method using Ant Colony Optimization -- 44. Gene Selection for Diagnosis of Cancer in Microarray Data using Memetic Algorithm -- 45. Handwritten Bangla City Name Recognition using Shape-Context Feature -- 46. Driver Safety Approach Using Efficient Image Processing Algorithms for Driver Distraction Detection and Alerting -- 47. Feature Selection using Histogram based Multi-Objective GA for Handwritten Devanagari Numeral Recognition -- 48. Extended Kalman Filter for GPS Receiver Position Estimation -- 49. Energy Detection based Spectrum Sensing for AWGN and MIMO Wireless Channel -- 50. Spectrum Sensing using Matched Filter Detection -- 51. Multi-Antenna system Performance under ICSIT and ICSIR channel conditions -- 52. Cloud Adoption: A Future Road MAP for Indian SMEs -- 53. A Computational Intelligent Learning Architecture in Cloud Environment -- 54. Performance Scrutiny of Source and Drain Engineered Dual-Material Double-Gate (DMDG) SOI MOSFET with Various High-k -- 55. Analysis of N + N - Epi-Source Asymmetric Double Gate FD-SOI MOSFET -- 56. Solar Tracking for Optimizing Conversion Efficiency Using ANN -- 57. Human Gesture Recognition in Still Images using GMM Approach -- 58. Design of Rate 3/4, 16 States, 16 PSK, Trellis Coded Modulation Code for AWGN Channel -- 59. Baseline Correction inEMG Signals using Mathematical Morphology and Canonical Correlation Analysis -- 60. Measuring discharge using Back propagation neural network: a case study on Brahmani river basin -- 61. Prediction of suspended sediment load using Radial basis neural network -- 62. A Hybrid Task scheduling approach based on Genetic Algorithm and Particle Swarm Optimization technique in Cloud Environment -- 63. Segmentation of Edema in HGG MR Images using Convolutional Neural Networks -- 64. Real Time Sign Language Gesture (Word) Recognition from Video Sequences Using CNN and RNN -- 65. Application of Soft Computing in Crop Management -- 66. A Hybrid Shadow Removal Algorithm for Vehicle Classification in Traffic Surveillance System -- 67. Real-time Analysis of a Non Linear State Observer with Improved Disturbance Compensation for Sensorless Induction Motor.
Keywords: Computational intelligence; Artificial intelligence; Dynamics; Nonlinear theories; Microprogramming .; Mobile computing; Computational Intelligence; Artificial Intelligence; Applied Dynamical Systems; Control Structures and Microprogramming; Mobile Computing